Impact of minimal invasive extracorporeal circulation on atrial fibrillation after coronary artery bypass surgery. Issue 11 (20th July 2020) - Ellam, Sten; Hartikainen, Juha; Korvenoja, Pekka; Pitkänen, Otto; Tyrväinen, Esko; Valtola, Antti; Halonen, Jari
Abstract: Postoperative atrial fibrillation (POAF) is the most common arrhythmia after cardiac surgery with an incidence between 15% and 50% and pathophysiology not fully known. By choosing the method of extracorporeal circulation with focus on the reduction of systemic inflammatory response, one can potentially decrease the risk of POAF. In this prospective, randomized trial, we compared minimal invasive extracorporeal circulation (MiECC) with conventional extracorporeal circulation (CECC) in the prevention of POAF after coronary artery bypass surgery (CABG). A total of 240 patients who were scheduled for their first on‐pump CABG, were randomized to MiECC or CECC. The primary outcome measure was the incidence of first POAF during the first 84 hours after surgery. POAF occurred in 42/120 (35.0%) MiECC patients and 43/120 (35.8%) CECC patients with nonsignificant difference between the groups (OR 1.043, 95% CI 0.591‐1.843, P = .884). The first postoperative creatine kinase‐MB mass (CK‐MBm) value was lower in the MiECC group, 13.95 [10.5‐16.7] (median [IQR]) than in the CECC group, 15.30 [11.4‐18.9] ( P = .036), whereas the use of perioperative dobutamine was higher in the MiECC group, 18/120 (15.0%), than in the CECC group 8/120 (6.7%) ( P = .038). The incidence of a stroke, perioperative myocardial infarction, and resternotomy caused by bleeding did not differ in the MiECC and CECC groups. Age (OR 1.08, 95% CI 1.04‐1.13, P = .000) and peak postoperative CK‐MBm (OR 1.57, 95% CI 1.06‐2.37, P = .026) were independent predictors of POAF. MiECC compared to CECC was not effective in reducing the incidence of POAF in patients undergoing CABG.